Abrazijska odpornost betonov na vodnih zgradbah - Kryžanowski, Andrej (Gradbeni vestnik, 2024)
The paper deals with the issues of concrete resistance to long-term abrasion loading caused by waterborne particles. The purpose of the research work is to define the criteria for the design of abrasion-resistant concrete linings for the proposed hydro power plants on the Sava River. The abrasion resistance of concrete was investigated in accordance with the standard ASTM C 1138 method. The research work was based on a comparison between laboratory results and measurements of the abrasion resistance of concrete under natural conditions by performing test plots in the stilling basin of the Vrhovo HPP. Concrete composites with different mechanical properties were analysed within the research programme. The basic composition of the concretes, which is the same as that of the spillway of the Vrhovo HPP, was modified by polymer or pozzolanic additives, as well as by the primary binder, steel fibers, polypropylene fibers and granular rubber. The analysis showed a qualitative similarity of the level of abrasion of concrete between laboratory simulations and field measurements, as well as suitability of the ASTM C 1138 laboratory method for assessing the abrasion resistance of concretes in the spillway of the HPP chain on the Lower Sava River.
Keywords: abrasion; abrasion resistance; abrazija; abrazijska odpornost; betoni; concrete; hydraulic structures; vodne zgradbe